ANALISIS RASIO AKTIVITAS TERHADAP PROFITABILITAS USAHA DAGANG CAHAYA UJUNGLOE KABUPATEN BULUKUMBA - Nurfitrah Nurfitrah; Jamaluddin Majid; Suhartono Suhartono (ISAFIR: Islamic Accounting and Finance Review, 2023)
Abstract, The purpose of this study was to analyze the effect of the activity ratio consisting of asset turnover, inventory management and receivables on the profitability ratio (Return on Assets) at UD Cahaya, Ujungloe District, Bulukumba Regency. The type of data used is in the form of quantitative data and secondary data sourced from UD Cahaya. The data collection technique used is the company's documentation technique in the form of a balance sheet and profit and loss report with descriptive data analysis techniques. Data analysis was performed by first analyzing financial ratios for the five-year current period. Then it was analyzed through multiple regression methods with the help of the SPSS V 21 statistical application to determine the effect between variables. The results of the study show that there is no significant effect between asset turnover variables on profitability. The inventory variable partially has a positive and significant influence on profitability in the Light Trading business. Meanwhile, the variable accounts receivable partially has a positive and significant influence on the profitability of the Cahaya trading company. These results prove that the parties in Cahaya's trading business have been able to manage their receivables and inventories effectively. However, in terms of asset management, it is still not optimal and is more influenced by other factors not mentioned in this study.